The Level of Knowledge of Football Match Rules in Referees of South Sulawesi Province Indonesia - Saharullah (PT Inovasi Pratama Internasional, 2023)
This study aims to determine the level of knowledge of football match rules in South Sulawesi Province referees. The main variable of this study is knowledge of the rules of football matches in South Sulawesi Province. The population in this study is all football referees under the auspices of the Provincial Association of the All Indonesia Football Association of South Sulawesi. While the sampling technique uses purposive sampling techniques with the samples used are 25 football referees in South Sulawesi Province. Based on the results of the analysis of the level of knowledge of football match rules, it can be categorized that of the 25 respondents are in the category that 2 respondents (8%) have a very less level of knowledge, 7 respondents (28%) have a less level of knowledge, 5 respondents (20%) have a moderate level of knowledge, 11 respondents (44%) have a good level of knowledge and 0 respondents (0%) have a very good level of knowledge. Knowledge of football match rules on South Sulawesi Province referees is in the